Identification of side- and shear-dependent microRNAs regulating porcine aortic valve pathogenesis - Rathan, Swetha (Sci Rep, 2016)
Aortic valve (AV) calcification is an inflammation driven process that occurs preferentially in the fibrosa. To explore the underlying mechanisms, we investigated if key microRNAs (miRNA) in the AV are differentially expressed due to disturbed blood flow (oscillatory shear (OS)) experienced by the fibrosa compared to the ventricularis. To identify the miRNAs involved, endothelial-enriched RNA was isolated from either side of healthy porcine AVs for microarray analysis. Validation using qPCR confirmed significantly higher expression of 7 miRNAs (miR-100, -130a, -181a/b, -199a-3p, -199a-5p, and -214) in the fibrosa versus the ventricularis. Upon bioinformatics analysis, miR-214 was selected for further investigation using porcine AV leaflets in an ex vivo shear system. Fibrosa and ventricularis sides were exposed to either oscillatory or unidirectional pulsatile shear for 2 days and 3 & 7 days in regular and osteogenic media, respectively. Higher expression of miR-214, increased thickness of the fibrosa, and calcification was observed when the fibrosa was exposed to OS compared to the ventricularis. Silencing of miR-214 by anti-miR-214 in whole AV leaflets with the fibrosa exposed to OS significantly increased the protein expression of TGFβ1 and moderately increased collagen content but did not affect AV calcification. Thus, miR-214 is identified as a side- and shear-dependent miRNA that regulates key mechanosensitive gene in AV such as TGFβ1.